Crime, punishment and social norms - Jörgen W. Weibull; Edgar Villa (Stockholm School of Economics, The Economic Research Institute (EFI), 2005)
We analyze the interplay between economic incentives and social norms when individuals decide whether or not to engage in criminal activity. More specifically, we assume that there is a social norm against criminal activity and that deviations from the norm result in feelings of guilt or shame. The intensity of these feelings is here endogenous in the sense that they are stronger when the population fraction obeying the norm is larger. As a consequence, a gradual reduction of the sanctions against criminal activity, or of the taxation of legal incomes, may weaken the social norm against crime. Due to the potential multiplicity of equilibria in our model, such a gradual change may even induce a discontinuous increase in the crime rate. We show that law enforcement policies may have dramatic and permanent efects on the crime rate, and lead to hysteresis. We also define political equilibrium under majority rule and show how a majority of individuals, who feel no guilt or shame from violating the law, in political equilibrium can exploit a minority who do have such feelings.
Keywords: D01; D11; D72; 330; crime; punishment; social norm; political equilibrium; Kriminalität; Strafe; Public Choice; Soziale Norm